Financial inclusion and income inequality in developing countries: the role of aging populations - Md Jamil, Abd Rahim; Law, Siong Hook; Khair-Afham, M.S.; Trinugroho, Irwan (Elsevier Inc., 2024)
This paper investigates how financial inclusion impacts income inequality by considering the role of an aging population as a moderator in 73 developing countries from 2004 to 2019. The generalized method of moments (GMM) estimator results reveal that financial inclusion and an aging population are insignificant determinants of income inequality. Nevertheless, the interaction effect between both variables on income inequality is substantial in these countries. Meanwhile, the empirical findings of a panel quantile regression indicate that financial inclusion and an aging population are significant determinants of reducing income inequality at low quantile levels. The aging population is essential in moderating the relationship between financial inclusion and income inequality, especially in increasing the income gap when countries’ inequality is lower; however, the coefficient values showed a downward-sloping trend toward high quantiles.